Analisis Penerapan Housekeeping sebagai Upaya Pencegahan Kecelakaan Kerja di Instalasi Rawat Inap Rumah Sakit Umum Daerah - Hrp, Nurul Arisanty; Mudayana, Ahmad Ahid (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2019)
Background: Installation of hospitalization had activities that required more attention in the implementation of occupational health and safety (K3) to reduce the variety of complaints from users of hospital services because of negligence that caused accidents. Accident prevention efforts to achieve the target K3 was done by the application of housekeeping. Region Public Hospital of Mandau, Bengkalis was a new class C hospital which functioned since 2008, so the application of housekeeping could help improve the quality of service. Method: This study used a qualitative descriptive method. Data collection techniques were in-depth interviews and observation. The sampling technique was by purposive sampling. Subjects were 13 and the validity of the data applied triangulation sources. Results: The analysis of the application with the principles of 5S housekeeping showed: 1) The application seiri (quick) has not done well since there were no separate bins; 2) The application of seiton (neat) has been performing well since neatness has been kept already; 3) The application of seiso (rehearsal) has not done well since the bathrooms were not cleaned regularly; 4) The application of seiketsu (care), and shiketsu (diligent) has not done well because it was based on 3S previously found that the application has not done well. Conclusion: Application of housekeeping as prevention of job accidents in the inpatient room of region public hospital has not done well because based on interviews and observations it was indicated that only application seiton (neat) was already performing well.